Impact of smartphone dependence on depression in Chinese adolescents with a moderated mediation model - Xuehui Li; Wenjuan Zhang; Wen Li; Shengkai Wang; Deng Pan (Scientific Reports)
Abstract In the digital age, smartphones have evolved into essential tools in contemporary society, raising significant concerns regarding their influence on daily life, particularly among adolescents. This research, drawing on the social-ecological systems theory, explored how smartphone dependence gradually impacted adolescent mental health under the combined influence of family and school environments.This study collected data from 3,770 high school students in China and analyzed it using SPSS along with the PROCESS. The results showed that smartphone dependence positively affected adolescent depression. Academic burnout and school belonging served as linked mediators in the relationship between smartphone dependence and depression. Moreover, parental involvement, serving as a moderating factor, played a significant role in the relationship between academic burnout and school belonging on adolescent depression. When parental involvement was low, the positive association between academic burnout and depression was substantial, as was the negative association between school belonging and depression. However, with higher levels of parental involvement, the positive effect of academic burnout on depression diminished, while the negative effect of school belonging on depression became more pronounced. These findings illuminated the psychological mechanisms that contributed to smartphone dependence and provided a theoretical framework for formulating interventions designed to alleviate depression in adolescents.